Synthesis and Characterization of Molybdenum Back Contact Using Direct Current-Magnetron Sputtering for Thin Film Solar Cells - Pandharkar, Subhash M.; Rondiya, Sachin R.; Rokade, Avinash V.; Gabhale, Bharat B.; Pathan, Habib M.; Jadkar, Sandesh R. (Frontiers in Materials, 2018)
In present work, we report synthesis of Mo thin films by DC-magnetron sputtering method. The structural, optical, morphological and electrical properties were investigated as a function of target-to-substrate distance. From the results, it is evident that with increase in target-to-substrate distance the thickness of films decreases while its sheet resistance and electrical resistivity increases, which is confirmed by van der Pauw method. Low angle XRD analysis revealed that with increase in target-to-substrate distance preferred orientation of Mo crystallites changes from (211) to (110) and its size decreases. The FE-SEM analysis revealed a significant change in surface morphology with increase in target-to-substrate distance. UV-Visible spectroscopy analysis showed that Mo films deposited at high target-to-substrate distance have more reflection than those deposited at lower target-to-substrate. Finally, adhesion test was performed using scotch hatch tape adhesion test which show all Mo films have excellent adhesion over the entire range of target-to-substrate distance studied. The employment of such Mo films as back contact can be useful to improve efficiency of CZTS solar cells.